2019
DOI: 10.1186/s12935-019-0782-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SNHG12 regulates the viability and invasion of renal cell carcinoma cells through modulation of HIF1α

Abstract: Background Cumulative evidences demonstrated the aberrant overexpression of Small Nucleolar RNA Host Gene 12 (SNHG12) in diverse human cancer. However, the expression status and involvement of SNHG12 in renal cell carcinoma is still elusive. Methods The expression of SNHG12 was determined by q-PCR. The transcriptional regulation was interrogated by luciferase reporter assay. Cell viability was measured with CCK-8 kit. The anchorage-independent was evaluated by soft agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…SNHG12 has various biological functions through targeting of cell proliferation, invasion, migration, and apoptosis. SNHG12 is involved in different types of malignant diseases by targeting the following microRNAs: miR-424-5p in cervical cancer (124), miR-320 in gastric cancer (125), miR-199a-5p in renal cell carcinoma (126), miR-199a/b in hepatocellular carcinoma (32), miR-199a/b in gastric cancer (127), miR-138 in lung cancer (32), miR-181a in lung cancer (128), miR-16-5p in thyroid carcinoma (129), miR-129-5p in laryngeal squamous cell carcinoma (130), miR-199-5p in renal carcinoma (126), and miR-195-5p in osteosarcoma (131).…”
Section: Small Nucleolar Rna Host Gene 12 (Snhg12)mentioning
confidence: 99%
“…SNHG12 has various biological functions through targeting of cell proliferation, invasion, migration, and apoptosis. SNHG12 is involved in different types of malignant diseases by targeting the following microRNAs: miR-424-5p in cervical cancer (124), miR-320 in gastric cancer (125), miR-199a-5p in renal cell carcinoma (126), miR-199a/b in hepatocellular carcinoma (32), miR-199a/b in gastric cancer (127), miR-138 in lung cancer (32), miR-181a in lung cancer (128), miR-16-5p in thyroid carcinoma (129), miR-129-5p in laryngeal squamous cell carcinoma (130), miR-199-5p in renal carcinoma (126), and miR-195-5p in osteosarcoma (131).…”
Section: Small Nucleolar Rna Host Gene 12 (Snhg12)mentioning
confidence: 99%
“…In prostate cancer, SNHG12 induced the activation of Wnt/β-catenin signaling to accelerate cell proliferation by absorbing microRNA-95 [27]. Likewise, an abundance of SNHG12 promoted viability, migration, and invasion both in ovarian cancer and renal cell carcinoma cells through regulation of miRNA-129/SOX4 axis and HIF1α, respectively [28,29]. Moreover, overexpression of SNHG12 induced by c-Myc facilitated proliferation and weakened cisplatin sensitivity in T-cell lymphoma by regulating Ki67/P-gp [30].…”
Section: Discussionmentioning
confidence: 99%
“…As depicted in Figure 5 (17), ovarian cancer (14), colorectal cancer (42), and osteosarcoma (18). Additionally, upregulated SNHG12 expression levels play important roles in the cellular process of tumorigenesis, including cancer cell proliferation (12,19,39,43), migration (18,37), invasion (36,38), apoptosis (16,44), epithelial-mesenchymal transition (EMT) (17) and chemoresistance (45).…”
Section: Online Cross-validation In Tcga Datasetmentioning
confidence: 99%
“…The present evidence revealed that SNHG12 could function as ceRNA by directly binding to miRNA and thereby regulating target genes in human cancers. For instance, SNHG12 upregulation increased the expression of hypoxia-inducible factor 1 α (HIF1α) by targeting miR-199a-5p, which induced cell proliferation, migration, and invasion in renal cell carcinoma (38). Moreover, doxorubicin resistance in osteosarcoma was promoted by SNHG12 via targeting miR-320a to upregulate myeloid cell leukemia 1 (MCL1) (45).…”
Section: Online Cross-validation In Tcga Datasetmentioning
confidence: 99%
See 1 more Smart Citation